Firm Characteristics and Financial Reporting Quality: A Case of Property and Real Estate Companies listed in Indonesian Stock Exchange - Putri, Cut Widy Aulia; Indriani, Mirna (Universitas Syiah Kuala, 2019)
Objective This study aims to investigate the impact of firm characteristics, namely leverage, profitability, and firm size, on financial reporting quality as measured by discretionary accruals.Design/methodology This sample of this study is Property and Real Estate companies listed in the Indonesian Stock Exchange (IDX) for the period of 2015 to 2017. In total, there are 36 firms chosen as the samples for this study or 108 observations. The data was analyzed using the multiple regression method.Results This study demonstrates that the leverage and profitability have significant impact on financial reporting quality, while firm size has no significant impact on financial reporting quality.